The Value of Piped Water and Sewers: Evidence from 19th Century Chicago - Coury, Michael; Kitagawa, Toru; Shertzer, Allison; Turner, Matthew A. (The Review of Economics and Statistics, 2024)
We estimate the impact of piped water and sewers on property values in late 19th century Chicago. The cost of sewer construction depends sensitively on imperceptible variation in elevation, and such variation delays water and sewer service to part of the city. This delay provides quasi-random variation for causal estimates. We extrapolate ate estimates from our natural experiment to the area treated with water and sewer service during 1874-1880 using a new estimator. Water and sewer access increases property values by a factor of about 2.8. This suggests that benefits are large relative to: the value of the value of averted mortality, many other infrastructure projects, and construction costs.